Manage Supply Chain Management Using Multi-Agent System for Multi-brand Retail - Sindhu, Ritu (International Journal of Computer Sciences and Engineering, 2025)
This paper describes an ongoing effort in developing a Multi-agent System (MAS) for supply chain management for Multi-brand retail. In our framework, several suppliers, dealers and retailers are involved in transportation of raw materials and goods from dealers to various stores. Agents must have the knowledge of various warehouses where goods are stored. Warehouses must be selected close to the store so that logistic and transports involved in the process get reduced. The ontology defines the domain area and set of rules to understand the mechanism and get the knowledge of information flow between agents.